Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1073
|View full text |Cite
|
Sign up to set email alerts
|

A robust self-learning method for fully unsupervised cross-lingual mappings of word embeddings

Abstract: Recent work has managed to learn crosslingual word embeddings without parallel data by mapping monolingual embeddings to a shared space through adversarial training. However, their evaluation has focused on favorable conditions, using comparable corpora or closely-related languages, and we show that they often fail in more realistic scenarios. This work proposes an alternative approach based on a fully unsupervised initialization that explicitly exploits the structural similarity of the embeddings, and a robus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
755
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 453 publications
(764 citation statements)
references
References 16 publications
7
755
1
1
Order By: Relevance
“…Morphological GeneralizationWe propose a novel quadripartite analysis of the BLI models, in which we independently control for four different variables: (i) word form frequency, (ii) morphology, (iii) lexeme frequency and (iv)10 We also used our dictionaries to train and test the more recent model ofArtetxe et al (2018b) on a handful of languages and observed the same general trends.11 We did this within the FASTTEXT framework, using the trained .bin models for each of our 10 languages.…”
mentioning
confidence: 99%
“…Morphological GeneralizationWe propose a novel quadripartite analysis of the BLI models, in which we independently control for four different variables: (i) word form frequency, (ii) morphology, (iii) lexeme frequency and (iv)10 We also used our dictionaries to train and test the more recent model ofArtetxe et al (2018b) on a handful of languages and observed the same general trends.11 We did this within the FASTTEXT framework, using the trained .bin models for each of our 10 languages.…”
mentioning
confidence: 99%
“…As table 7 shows, there are no improvements among above methods. Some linear mapping Approach EM F1 MUSE 33.03 49.48 DeMa (Zhou et al, 2019) 55.64 72.59 Vecmap (Artetxe et al, 2018) methods even causes devastating effect on EM/F1 scores.…”
Section: A23 Discussionmentioning
confidence: 99%
“…The input of our method is a set of cross-lingual word embeddings and the monolingual corpora used to train them. In our experiments, we use fastText embeddings (Bojanowski et al, 2017) mapped through VecMap (Artetxe et al, 2018b), but the algorithm described next can also work with any other word embedding and cross-lingual mapping method.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The resulting cross-lingual embeddings are then used to induce the translations of words that were missing in the training dictionary by taking their nearest neighbor in the target language. The amount of required supervision was later reduced through self-learning methods (Artetxe et al, 2017), and then completely eliminated through adversarial training (Zhang et al, 2017a; or more robust iterative approaches combined with initialization heuristics (Artetxe et al, 2018b;Hoshen and Wolf, 2018). At the same time, several recent methods have formulated embedding mappings as an optimal transport problem (Zhang et al, 2017b;.…”
Section: Related Workmentioning
confidence: 99%